Doing it differently: A farmer-focused, private sector-driven approach to delivering innovation that works for women in the smallholder chicken value chain - Sonaiya, Emmanuel B.; Goromela, E.H.; Assefa, G.; Bamidele, O.; Mbaga, S.H.; Abegaz, Solomon; Negawo, Alemayehu T.; Getachew, Fasil; Dessie, Tadelle (2019)
The African Chicken Genetic Gains (ACGG) program is built on five “pillars of change”. The first pillar is to make available high producing tropically adapted breeds (hpTAB). The second pillar is to determine farmer-preferred hpTAB. The third pillar is to create public-private partnerships for the delivery of services in the smallholder chicken value chain (SCVC). The fourth pillar is to ensure direct involvement of women in program decisions at all levels. The fifth pillar is the use of an innovation platform for co-creation of solutions with actors of SCVC. Implementation of ACGG in Ethiopia, Nigeria and Tanzania produced significant results in: breed testing by 6,348 smallholders in their own system; chick brooding by 20 mother units; access to finance/markets through the formation of 60 cooperatives and their linkage with microfinance institutions, aggregators and processors; mainstreaming poultry vaccination programs by policy changes that allow use of community animal health workers (CAHW) in Nigeria that previously did not authorize them; opportunities for government livestock regulators to connect with SCVC actors in the villages. ACGG has contributed to the methodology for addressing the challenges and underlining the opportunities and prospects for partnerships between smallholder and commercial poultry in order to improve livelihood of women in the rural communities and the growth of the African economy.